Construct Validity Evidence for the Student Aspirations Survey - Jonathan A. Plucker (Journal of Research in Rural Education, 1996)
The influence ofstudents' affective development-especially student aspirations -upon academic and life achievement is gaining significant attention in the literature. However, psychometrically sound instruments that measure student aspirations and students perceptions ofschool climate characteristics that influence aspirations are not available for use by educators attempting to guide school reform efforts. The Student Aspirations Survey was administered to 1,160 students in two rural middle and two rural high schools. Responses were subjected to confirmatory factor analysis, and results suggest that evidence ofconstruct validity is considerable for student responses to the aspirations scales and very limited for student responses to the school climate scales (possibly due to the very high factor correlations). A small to moderate method effect may be present among student responses to the aspirations scales. Suggestions for improvement ofscore interpretation are provided.